Analyzing Customers’ Acceptance towards Task Management Application Using Affective Technology Acceptance Model (ATAM) - Setiawan, Iwan; Soebana, Heri; Maskur, Maskur (Interdisciplinary Social Studies, 2021)
Background: State the reason why the research needs to be conducted. Aim: This study aims to explain and analyze the influence of user perceptions of PT Collega Inti Pratama employees on attitudes and use of Task Management applications. Method: This study uses quantitative analysis and data sampling using the saturated sample method. Samples taken from the respondents’ data are users of the Task Management application. Data collection techniques using a questionnaire. In data analysis, researchers used multiple linear regression analysis techniques and path analysis in proving the mediating variable. Findings: The results show that simultaneously Positive Affect and Negative Affect have an effect on Perceived Ease of Use. Perceived Ease of Use, Positive Affect and Negative Affect influence together on Perceived Usefulness. Perceived Usefulness and Perceived Ease of Use jointly affect Attitude Toward Using. Positive Affect, Negative Affect and Attitude Toward Using together influence Behavioral Intention.